Synthesis of (phosphonomethyl)phosphinate pyrophosphate analogues via the phospha-Claisen condensation. Issue 3 (13th November 2014) - Gelat, Fabien; Lacomme, Claire; Berger, Olivier; Gavara, Laurent; Montchamp, J.-L.
Abstract : Pyrophosphate analogues are of great importance especially for the design of biologically active molecules. Abstract : Pyrophosphate analogues are of great importance especially for the design of biologically active molecules. The phospha-Claisen condensation allows for the rapid synthesis of (phosphonomethyl)phosphinate pyrophosphate analogues and building blocks that can be employed in numerous applications.